Public-Private Partnership in the Water Supply Sector of Ghana: Has IT Delivered Public Accountability? - Lamptey, E. (University of Ghana, 2018)
Accountability and transparency have long remained an area of concern in public-private partnerships (PPP). In addition, there is a concern in the literature to examine accountability from a developing country’s perspective. This thesis responds to the call by drawing on the Shaoul et al’s (2012) governance-based reporting framework which has received little application in literature to examine the extent to which PPP delivers public accountability in water supply sector. The study focuses on the water supply sector as it remains the only sector that has seen the most successful private sector participation in Sub-Saharan Africa, particularly in Ghana. The main objectives of the study are to examine that extent to which PPP in the water supply sector provide public accountability and possible challenges with associated implications for accountability. In order to achieve the objectives of the study. The researcher adopts a single case study approach, which is based on the qualitative methodology involving the use of interviews and documentary analysis. The findings shows that there is a limited disclosure and transparency of information in the water supply sector in Ghana due to “commercial confidentiality”. The lack of information about PPP transaction in the water supply sector reduces the public ability to make an informed decision and pass judgements on PPP transactions. Secondly, findings reveal that there is a lack of public consultation in PPPs in the water supply sector, particularly as citizen and taxpayer do not speak with a unified voice. Thirdly, the finding of the study reveals that PPPs lack the right institutional framework. As a result, unsolicited PPP projects are relatively expensive compared to traditional competitive tendering, creating affordability challenges for the citizens. Fourthly, the finding from the study reveals that key institutions, such as the Audit Service of Ghana, are not involved in the evaluation and monitoring of PPP transactions to ensure value for money. In addition, the external evaluation is undermined by the lack of information in the public domain. The study provides several opportunities for further studies. In future, other studies can draw on the governance-based reporting framework to examine accountability practice in other important sectors of the economy. In addition, future studies can centre on how the clash of organizational culture between the public and private may complicate accountability within the context of PPP.
MPhil.
Keywords: Public-Private Partnership; Water Supply Sector; Ghana; Public Accountability